Toxins and Venoms from Marine Cnidarians and Gastropods: Diversity and Potential Drugs Targeting the Ion Channels - Tlili, Sofiene; Ben Brahim, Raoua; Sabatier, Jean-Marc; Regaya, Imed (Venoms and Toxins, 2022)
A diversity of marine invertebrates, such as cnidarians are rich sources of large bio-active molecules. This chemo-diversity of bio-active compounds has a promising potential in several biotechnological and therapeutic applications. On the basis of a comparative bibliographic approach, we intend in this review to present and discuss an overview of: i) the diversity of marine invertebrates as a candidate for bio-active molecules production; ii) the diversity of bio-active compounds and venom derived from these organisms; iii) the relationship between, the diversity of these marine organisms and the structure of the toxins they secrete. In this bibliographic study, a focus is going to be made on protein neurotoxins targeting ion channels. We also discuss the potential link between the bioecological characteristics of cnidarians and the diversity of toxins.
Keywords: venoms